2005
DOI: 10.1080/13506280444000814
|View full text |Cite
|
Sign up to set email alerts
|

Toupee or not toupee? The role of instructional set, centrality, and relevance in change blindness

Abstract: The influence of instructional set, centrality, and relevance on change blindness was examined. In a one-shot paradigm, participants reported alterations of items across pairs of driving scenes under two different instructional conditions. Alterations involved either relocations or disappearances of the same items and included driving-relevant and driving-irrelevant alterations to items of central and marginal interest. Three main findings emerged: Centrality was not a function of driving relevance/meaningfuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
10
1
Order By: Relevance
“…Pearson and Schaefer (2005) showed that participants' involvement in a change-blindness task on photographs of road scenes modified their performance. Participants in the so-called cognitive-engagement condition were told that the results of the study might be of diagnostic value in identifying people in need of remedial driver training.…”
Section: Discussionmentioning
confidence: 98%
“…Pearson and Schaefer (2005) showed that participants' involvement in a change-blindness task on photographs of road scenes modified their performance. Participants in the so-called cognitive-engagement condition were told that the results of the study might be of diagnostic value in identifying people in need of remedial driver training.…”
Section: Discussionmentioning
confidence: 98%
“…Also, a wider scope of attention and cultural tendencies to a more holistic processing can alleviate change blindness in the periphery of the visual field (Masuda & Nisbett, 2006;Zelinsky, 2001). Interestingly, so too does intelligence (Zhu et al, 2010), proofreading experience (Asano, Kanaya, & Yokosawa, 2008), attention to detail as in Asperger syndrome (Fletcher-Watson et al, 2012;Smith & Milne, 2009) and an appropriately formulated set of instructions emphasizing task centrality (Pearson & Schaefer, 2005). These studies suggest that the bottom-up effects could be enhanced by a certain attentional mindset or acquired individual abilities, and change detection performance improved accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Eyewitness researchers should take note of the relevance of change blindness research and theory to cases of mistaken identification, and change blindness researchers could use the finding of eyewitness researchers that cognition and simple vigilance both play a role in inducing change blindness (cf. Pearson & Schaefer, 2005).…”
Section: Discussionmentioning
confidence: 99%